ANALISIS TEKNIS DAN EKONOMIS PRODUKSI ARANG AKTIF INDUSTRI PEDESAAN - Tjutju Nurhayati; Saepuloh Saepuloh; Sylviani Sylviani (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
The objectives of this trial was to produce activated charcoal from 5 raw material species which are abundantly potential. The production was conducted in an experimentally designed kiln, expectedly appropriate as a manufacturing prototype of activated charcoal for the inherent endeavors or small-scale village industries, which would be feasible technically, economically, and environmentally. The parameters related to the technical analysis covered the manufacture of charcoal from three wood species (bakau, mangium, and tusam) and coconut shell; analysis on raw material for such charcoal and on the mixed charcoal from the market; activation process using water vapor and air at consecutively 0.25 bar and 4-5 atmospheric pressures, with the temperature as high as 705-805°C; and analysis on iod number for the quality of activated charcoal. For economic evaluation, the inherent parameters covered production cost, activated charcoal price, and other related aspects. For the comparative assessments were used activated charcoals from sawdust and coconut shell from industry. The results are as follows: